Aplikasi Visualisasi Pembangunan Jalan Baru Menggunakan Augmented Reality - Hidayat, Dandi; Setiawan, Debi; Arisandi, Diki (Yayasan Rahmatan Fidunya Wal Akhirah, 2023)
Augmented Reality Technology that combines the real world with the virtual world, is interactive in real time, and is in the form of 3D animation. The Markerless Augmented Reality method is also called the markerless method, with this method the user no longer needs to use a marker to display digital elements. Currently, the construction of a road still uses a lot of rough drawings or designs using paper prints. The problem faced by workers is that drawings for making new roads use design drawings in 2D which are printed on paper, paper is prone to damage if it is always taken to the work site, such as being exposed to water, dust and folding which could damage the image on the printed paper. The research that will be carried out uses Augmented Reality technology which can provide information in the form of 3D road pavement images as well as information about the layers that make up the road pavement.